Extremely Long-Closed Galls of a Social Aphid. (3rd September 2009) - Kurosu Kurosu, Utako Utako; Aoki Aoki, Shigeyuki Shigeyuki
Abstract : The aphid Nipponaphis monzeni (Hormaphidinae, Nipponaphidini) forms large, hard, completely closed galls on the evergreen Distylium racemosum, its primary host, in south-western Japan. By marking 100 galls on a tree and monitoring them over five years, and by sampling many immature galls from another tree in various seasons and dissecting them, we found that galls of N. monzeni are initiated in June, that they remain small for at least 21–22 months and that tiny fundatrices survive for over one year. Some galls rapidly expand during April/May in the third year. Others remain small and swell up in the fourth year and still others in the fifth year. Full-grown galls open in November/December, and alates fly to evergreen oaks, the secondary host. Thus galls of N. monzeni take 2.5 years to mature at earliest (3-year life cycle) and some galls 3.5 or 4.5 years (4- or 5-year life cycle).